Bisalkynylated 3,6-diiminocyclohexa-1,4-diene-1,4-diamine - Biegger, Philipp; Schaffroth, Manuel; Brödner, Kerstin; Tverskoy, Olena; Rominger, Frank; Bunz, Uwe H. F. (Chemical communications, 2015)
Reduction of bis(benzothiadiazol) by LiAlH4/CuI gives diethynylated diaminobenzoquinoneimine. This building block accesses novel targets in a one-step condensation reaction with different ortho-quinones, resulting in unexpected rearrangement products. The compounds are characterized by their photophysical and electrochemical data as well as quantum chemical calculations.
Gesehen am 25.05.2020